Human rights centered global governance of quantum technologies: advancing information for all - UNESCO (2025)
Quantum technologies—encompassing quantum computing, communications, sensing, and materials—represent a groundbreaking frontier with the potential to revolutionize industries such as healthcare, energy, finance, and communications. However, like all transformative innovations, they come with opportunities, challenges and implications for human rights.
Worldwide